Proceeding the 1st international seminar on chemical education 2015 (ISCE 2015) : chemistry education as an industry development's agent in Indonesia, Yogyakarta 30th September 2015 / editor, Dwiarso Rubiyanto...[et.al] - Dwiarso Rubiyanto (Department of Chemistry Education Faculty of Mathematics and Natural Sciences Universitas Islam Indonesia, 2015)
xi, 255 halaman : ilustrasi, tabel, grafik ; 30 cm